Evaluación técnico económica de una nueva mezcla entre la gasolina actual, Jet Fuel A-1 y bioetanol cumpliendo la resolución 40103 aplicando la técnica de espectroscopia infrarroja FT-IR. (2022)
For this research project, there is a proposal for a fuel used in gasoline-type internal combustion vehicles optimized in quality and price, taking into account that only two types of fuel are offered in the Colombian fuel market, regular gasoline, normal type, which It offers a minimum of 81 octane according to resolution 40103 of the Ministry of Mines and Energy. In the case of extra type gasoline, it allows a minimum of 91 octane, which is verified by the test method ASTM D2699-19 and ASTM D2700-19, in addition to the tests allowed by the Ministry of Mines and Energy in which a single cylinder to verify the IAD also clarifies the alternate use of the ft-ir infrared spectroscopy technique for the determination of said antiknock index.